Case studies in restraint use in an acute teaching hospital : a Foucauldian approach - Irving, Kate (Curtin University, 2001)
This thesis reports the outcomes of research into the use of restraint in the care of patients in an acute teaching hospital in Australia. The literature review undertaken for the study revealed much research into restraints showing evidence of the harm they cause, and their ineffectiveness as a safety measure. The literature indicates that the prevalence of restraint use is high - about a third of all hospital patients over the age of eighty-five years may be restrained at some time during the period of their admission.The main emphasis in my investigation was to uncover an understanding of how the use of restraints has remained possible, despite negative reports on their efficacy and questions about their possible abuse of human rights. Primarily, 1 set out to provide vide an understanding of restraint practice, and of how it is maintained and legitimised in a metropolitan teaching hospital.The study was guided by a Foucauldian approach to discourse analysis. The study reports on in depth studies of three patients. The case studies extend beyond observations of the patients to include interviews with members of the multidisciplinary team: nurses, doctors, occupational therapists and physiotherapists. Medical and nursing notes were another source of data.A discursive formation was identified by which restraint use is justified, and legitimised by the health professionals who use it. Five discourses were established, constituting: inability to 'self govern'; an appropriate environment; treatment; duty of care; and marginalisation.The study concludes that restraint use can be understood as a complex discursive practice. Through this discursive practice we can understand how staff maintain a monopoly over the truth and perpetuate claims about the inevitability of restraint use. Knowledge of these discursive practices enables an understanding of how the current educational approaches to restraint reduction are likely to have little immediate or sustained impact. With these understandings, we are hopefully better placed to change practice in a way that does not substitute one undesirable approach for another. If this is so, the value of this thesis will lie in its influence on practice as much as in its contribution to scholarship.